Food Handlers Hygiene of Balinese Traditional Food in Tourism Destination at Badung Regency - Noviyanti Ni Putu Ayu Wulan; Febianingsih Ni Putu Eka; Dewi Putu Ratna Suprima (Babali Publisher, 2023)
Introduction: Food safety is the domain of public health problems which can be seen from the incidence of foodborne diseases that often occur in developing countries. Personal hygiene can prevent the occurrence of food borne diseases and cross contamination. This study aims to describe the food handlers hygiene while processing balinese traditional food. Methods: Observational research with cross sectional design. Respondents in this study are 90 food handlers in Badung Regency, obtained by purposive sampling. Descriptive statistical analysis and chi-square test was used in data analysis. Results: 20% food handler had good practice in personal hygiene while processing traditional food. Less than 100% food handlers wash their hands before and after cooking, wash their hands with soap, sneeze not facing food, and keep their nails clean and not long. 22,2% food handler uses hair net while processing food. 100% of food handlers are in good health and use clean clothes when processing food. There are differences in personal hygiene behavior based on education level (p=0,042). Conclusion: Traditional Balinese food handlers have low personal hygiene. Monitoring is needed to improve the hygiene of food handlers in the production processes. Analytical observational research is essential to understand the factors that influence food handler hygiene.